Molecular-Genetic Aspects of Breast Cancer - Krasteva M. (Sciendo, 2014)
Breast cancer is the most frequent malignancy among women. Advances in breast cancer knowledge have deciphered the involvement of a number of tumor suppressor genes and proto-oncogenes in disease pathogenesis. These genes are part of the complex biochemical pathways, which enable cell cycle control and maintenance of genome integrity. Their function may be disrupted as a result of alterations in gene sequence or misregulation of gene expression including alterations in DNA methylation pattern. The present review summarizes the main findings on major breast cancer related genes BRCA1/2, p53, ATM, CHEK2, HER2, PIK3CA and their tumorigenic inactivation/activation. The potential clinical importance of these genes with respect to patients’ prognosis and therapy are also discussed. The possible implication of other putative breast cancer related genes is also outlined. The first elaborate data on the genetic and epigenetic status of the above mentioned genes concerning Bulgarian patients with the sporadic form of the disease are presented. The studies indicate for a characteristic mutational spectrum in some of the genes for the Bulgarian patients and specific correlation between the status of different genes and clinicopathological characteristics.